1992
DOI: 10.1111/j.2042-7158.1992.tb03238.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric H+, K+-ATPase inhibition by catechins

Abstract: Five catechins, (+)-catechin, (-)-epicatechin, (-)-epicatechin gallate, (-)-epigallocatechin and (-)-epigallocatechin gallate, inhibited gastric H+, K(+)-ATPase activity with IC50 values ranging from 1.7 x 10(-4) to 6.9 x 10(-8) M, with (-)-epigallocatechin gallate as the most potent inhibitor. The intensity of inhibitor activity paralleled the number of phenolic hydroxy groups in the molecule. The inhibition of the enzyme by (-)-epicatechin was competitive with respect to ATP and noncompetitive with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…In vitro, tea catechins can inhibit carbohydrate digestive enzymes, such as salivary a-amylase, intestinal sucrase, a-glucosidase, and gastric H + ,K + -ATPase [124][125][126]. Using a rat everted sac, Kobayashi et al [127] showed that green tea polyphenols, especially ECG and EGCG, inhibited the sodium-dependent GLUT (Na bit intestinal brush-border membrane vesicles to demonstrate that 1 mM of ECG or EGCG reduced the glucose uptake by 53 and 35%, respectively, whereas no effect was observed after C and EGC treatments.…”
Section: Modulation Of Carbohydrate-related Enzymes and Transportersmentioning
confidence: 99%
“…In vitro, tea catechins can inhibit carbohydrate digestive enzymes, such as salivary a-amylase, intestinal sucrase, a-glucosidase, and gastric H + ,K + -ATPase [124][125][126]. Using a rat everted sac, Kobayashi et al [127] showed that green tea polyphenols, especially ECG and EGCG, inhibited the sodium-dependent GLUT (Na bit intestinal brush-border membrane vesicles to demonstrate that 1 mM of ECG or EGCG reduced the glucose uptake by 53 and 35%, respectively, whereas no effect was observed after C and EGC treatments.…”
Section: Modulation Of Carbohydrate-related Enzymes and Transportersmentioning
confidence: 99%
“…Several recent reviews have highlighted this activity. Detailed studies [62][63][64] have revealed that quercetin exerted a dose-dependent inhibition of growth and colony formation. The flavonoids, kaempferol, catechin, toxifolin and fisetin, also suppressed cell growth 65,66 .…”
Section: Antineoplastic Activitymentioning
confidence: 99%
“…The intensity of inhibitor activity parallels the number of phenolic hydroxy groups in the molecule. These findings suggest that the anti-secretory and anti-ulcerogenic effects of catechins are due to their inhibitory activity on gastric H+, K(+)-ATPase (14).…”
Section: Discussionmentioning
confidence: 76%